An exploratory study into the relationship between playing at home or away and concussion. (12th May 2023) - Howarth, Nathan; White, Adam J; Batten, John; Pearce, Alan J; Miller, Michelle A
ABSTRACT: Primary Objective: To investigate the effect of home and away game travel on risk of concussion across different levels of rugby union. Research Design: Exploration study across school, university, and professional rugby teams. Methods and Procedures: Retrospective analysis of concussion incidence and symptomology of surveillance data and prospective data collection for potential concussions via surveys. Data was collected from school rugby teams ( n = 344 matches, over 2 years), a university rugby ( n = 6 matches), and a professional rugby team ( n = 64 matches, over two seasons). Main Outcomes and Results: School level rugby had an increased prevalence of concussions in away matches ( p = 0.02). Likewise, there was a significant increase ( p < 0.05) in concussions at away matches in university rugby. In addition, the professional rug by team had significant differences in recovery times and symptoms with away fixtures, including longer recovery times ( p < 0.01), more initial symptoms ( p < 0.01), as well as greater and more severe symptoms at 48 hours ( p < 0.05). Conclusions: This research highlights an increased prevalence of concussion in school and university-aged rugby players away from home, as well as increased symptoms, symptom severity, and recovery times in professional rugby players.